Primary epithelioid trophoblastic tumor of the lung: A case report - Qiongying Zhang; Wenwen Sun; Zhen Zhang; Jianmin Li (Indian Journal of Pathology and Microbiology, 2024)
Primary epithelioid trophoblastic tumor (ETT) of the lung is exceedingly rare. Only about three cases have been reported in Pubmed and worldwide literature. We presented a case of multiple primary ETT of the lung occurring in a 33-year-old Chinese female patient. Comprehensive physical examinations revealed no evidence of a primary lesion on the uterus or cervix uteri. Microscopic examination of the tumor demonstrated ETT of the lung, which was confirmed by immunohistochemical staining and declining level of beta-human choriogonadotropin (β-HCG) after the operation. Our case revealed that the ETT can occur in the lung and should be considered when a female had a tumor of lung with increasing β-HCG.